PEMBERDAYAAN EKONOMI DI PESANTREN NURUL IKHLAS CANDI SIDOARJO - Nurul Inayah; Nawal Ika Susanti; Munawir Munawir (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Now several Islamic boarding schools in Indonesia, have begun to practice skills education. With the intention that, the santri not only strengthen themselves in the field of general education and Islamic religious scholarship, but have the skills (skill education) that are currently needed. The purpose of this study is to find out that currently several Islamic boarding schools in Indonesia, have practiced (skill education) with the mission that, the students not only strengthen themselves in the field of general education and religious knowledge, but have skills (skill education). The type of research used is qualitative research with descriptive method. As for this study using primary and secondary data sources. The analytical technique used in this research is interactive model analysis. The results of this study can be seen from the Nurul Ikhlas Islamic Boarding School which is able to empower students and the surrounding community, such as dragon fruit cultivation, salted egg making services with many flavors, cooperatives, animal husbandry and plantations. From the results of the research conducted, it can be concluded that the Nurul Ikhlas Islamic Boarding School has a big role in empowering the community, including the economically and educationally weak groups. This is in accordance with the spirit of Islam in elevating the welfare of the weak. As practiced by pesantren, namely helping underprivileged students.